A Quantitative Analysis of Brand Ambassador Effectiveness: The Lemonilo and NCT Dream Case - Sutrisno, Julius; Venesia , Eunike; Sena , Pieter; Hasugian, Dedy Saputra (APPS Publications, 2024)
Objective This study aims to analyze the influence of NCT Dream as brand ambassadors on organic instant noodle Lemonilo buying decisions and intention to purchase Lemonilo, and to determine the effect of intention on purchasing decisions from Lemonilo. Methodology This research uses quantitative methods with a quantitative descriptive analysis approach. The type of research is explanatory research which aims to explain the relationship between research variables. The research samples were taken randomly from the population. Data collection was carried out through an online survey using Google Forms. Findings The findings demonstrated that Lemonilo buying decision is positively and significantly impacted by NCT Dream as brand ambassadors and consumers’ buying interest, and consumers’ buying interest is positively and significantly influenced by NCT Dream as brand ambassadors. Novelty The quantitative analysis of the influence of brand ambassador on buying decisions and purchase intention speficially for the Lemonilo brand is the novelty of the research.